ACCOUNTING AND ECONOMICS RECIPROCALLY INDEBTED. - Perry, Kenneth W. (The Accounting Review, 1958)
Forces, both within the accounting profession and without, are constantly subjecting the accountant to ever-increasing pressures in an attempt to induce him to change some of his basic principles. Many of these forces can be attributed, either directly or indirectly to economists. It is the writer's belief that accounting and economics are more closely related and thus more interdependent than is commonly thought. It is also his belief that if the accountant and the economist were both more aware of their relationship and interdependency, both might derive mutual benefit there-from. Both accounting and economics are concerned with property and with human activities relating to the production, exchange, and consumption of this property. Generally speaking it is the point of view that differentiates one from the other. Whereas economics treats a society as a whole, of wealth in general, of the wants of people, and the satisfaction of those wants; accounting treats the individual units in society, the property of each unit, the requirements of each unit, and the efforts and accomplishments of each unit.